UiTM Global News : Engaging the world (Vol. 4 June 2020) - UiTM, Office of International Affairs (Office of Intenational Affairs, 2020)
Despite the tremendous fear COVID-19 inflicted on us, it has had a positive effect on humanity. It has created a high social sensitivity and responsibility amongst the UiTM community. Staff and students adopted new normal practices to benefit all. These unsung heroes at UiTM provided their support for the government and local communities via Initiatives and Community Social Responsibility (CSR) projects. These projects were developed to help front-liners care for COVID-19 patients. The innovative initiatives such as producing Protective Personal Equipment (PPE), hand sanitizers, and face protectors rippled across UiTM campuses. They played significant roles in meeting public needs during this calamity and their small gestures have had a huge impact on society.